CITRA PEREMPUAN DALAM NOVEL PULANG KARYA LEILA S. CHUDORI - Novera, Dian; Hayati, Yenni; Nst., Muhammad Ismail (Universitas Negeri Padang, 2017)
This research aims to describe (1) structures of novel of Pulang by Leila S. Chudori, (2) image of women as personal, and (3) image of women as society member. Theoritical studies used in this research are: (1) the essence of novel including: (a) the definition of novel and (b) substance of novel, (2) sociology of literature, (3) fiction analysis approach, (4) image of women, (5) women as personal, (6) image of women in social structure, (7) image of women in Javanese culture, and (8) critics of feminism literature. Type of this research is qualitative research which uses descriptive method. The data in this research are in form of words, phrases, clauses, and sentences which indicate image of women. The source of this research is novel Pulang by Leila S. Chudori. The data were collected by using descriptive method which prioritized the comprehension toward interconcept interaction which was examined empirically. The results of this research are: image of women in novel Pulang by Leila S. Chudori as follows: image of women as personal, women who have beauty, women who are gentle, and women who are modest and image of women as society member: relationship with family/society circle and care about family/society circle which take role as a child, as an older sister, as a younger sister, as a wife, as a mother, as a seller, as a guest, and as a host.Keywords: image, women, personal, society member, novel